2021
DOI: 10.1182/blood.2020007362
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced bystander effects impair transplanted human hematopoietic stem cells via oxidative DNA damage

Abstract: Total body irradiation (TBI) is commonly used in host conditioning regimens for human hematopoietic stem cell (HSC) transplantation to treat various hematological disorders. Exposure to TBI not only induces acute myelosuppression and immunosuppression but also impairs the various components of the HSC niche in recipients. Our previous study demonstrated that radiation-induced bystander effects (RIBE) of irradiated recipients decreased the long-term repopulating ability of transplanted mouse HSCs. However, RIBE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 52 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…We observed bystander effects on oxidative stress responses (or oxidation-reduction processes) with their 21 involved proteins (Table 2). Bystander activation of these responses has been observed in other model systems, recently in HepG2 and normal liver cells [36], human hematopoietic progenitor and stem cells [37] and mice exosomes [38].…”
Section: Implication Of Stress Granules Il12 Pathway and Oxidative St...mentioning
confidence: 72%
“…We observed bystander effects on oxidative stress responses (or oxidation-reduction processes) with their 21 involved proteins (Table 2). Bystander activation of these responses has been observed in other model systems, recently in HepG2 and normal liver cells [36], human hematopoietic progenitor and stem cells [37] and mice exosomes [38].…”
Section: Implication Of Stress Granules Il12 Pathway and Oxidative St...mentioning
confidence: 72%
“…More importantly, Cheng et al. ( 36 , 37 ) found that in transplanted human HSCs, radiation-induced bystander effects increased ROS levels, contributing to HSC damage and a decrease in transplantation efficiency. It has been hypothesized that forkhead homeobox type O transcription factors are key mediators of ROS regulation in HSCs, contributing to stem cell maintenance and the DNA damage repair response ( 38 ).…”
Section: The Seedmentioning
confidence: 99%
“…To prevent xenogenic donor-cell rejection and to allow for their settlement in the bone marrow niche, immune deficient animals are used to prevent graft rejection, and recipient mice need to be conditioned using irradiation or chemical treatment before transplantation similar to syn-and congenic transplantation models. However, as described above, such conditioning is toxic for sinusoidal blood vessels and MSCs in the murine stem cell niche (Yin et al, 2020) and, importantly, it impairs the function of xenogenic donor HSCs promoting their senescence and apoptosis by increasing ROS levels and mitochondrial damage (Hu et al, 2021).…”
Section: Xenograft Models: Human Hsc Engraftment In the Murine Bm Nichementioning
confidence: 99%